COMPARATIVE ANALYSIS OF THE DIAGNOSTIC VALUE CLINICAL GRADING SCALES FOR FACIAL NERVE AT CHILDREN WITH FACIAL NERVE NEUROPATHY - Liskevych, I. I.; Pityk, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article there is the comparative analysis of major national and foreign clinical scales of assessment of "facial nerve - facial muscles" dysfunction, considered the advantages and disadvantages of using these scales in clinical practice.